'[…] the situation in the schools still remains the Achilles heel.' Barriers to the implementation of school tobacco policies—a qualitative study from local stakeholder's perspective in seven European cities. Issue 1 (14th January 2020) - Hoffmann, Laura; Mlinarić, Martin; Mlard, Nora; Leo, Teresa; Grard, Adeline; Lindfors, Pirjo; Kunst, Anton E; Richter, Matthias
Abstract: School tobacco policies (STPs) are a crucial strategy to reduce adolescents smoking. Existing studies have investigated STPs predominantly from a school-related 'insider' view. Yet, little is known about barriers that are not identified from the 'schools' perspective', such as perceptions of local stakeholders. Forty-six expert interviews from seven European cities with stakeholders at the local level (e.g. representatives of regional health departments, youth protection and the field of addiction prevention) were included. The analysis of the expert interviews revealed different barriers that should be considered during the implementation of STPs. These barriers can be subsumed under the following: (i) Barriers regarding STP legislature (e.g. inconsistencies, partial bans), (ii) collaboration and cooperation problems between institutions and schools, (iii) low priority of smoking prevention and school smoking bans, (iv) insufficient human resources and (v) resistance among smoking students and students from disadvantaged backgrounds. Our findings on the expert's perspective indicate a need to enhance and implement comprehensive school smoking bans. Furthermore, collaboration and cooperation between schools and external institutions should be fostered and strengthened, and adequate human resources should be provided.